Konsep Ismah Nabi Muhammad (S.A.W) dalam Al-Quran - Wan Ali, Wan Z. Kamaruddin (Jurnal Usuluddin, 1997)
This article aims to discuss the concept of ismah (immunity from sin) of the prophets and messengers from the viewpoint of the Qur an. Emphasis is given to the views of the theologians from different streams of thought with regard to the above concept and evidences of the ismah of the prophets. Particular attention is also paid to the interpretation of ismah of the Holy Prophet Muhammad (p. b. u. h).